Tips and Tricks of Inflatable Penile Prosthesis Reservoir Placement: A Case Presentation and Discussion. (28th February 2014) - Simon, Ross; Hakky, Tariq S.; Henry, Gerard; Perito, Paul; Martinez, Daniel; Parker, Justin; Carrion, Rafael E.
Abstract Introduction There have been many advances in the inflatable penile prosthesis (IPP) since the 1970s. While these devices were initially fraught with mechanical malfunction, the most recent models prove to be much more reliable. Although reservoir complications are not common, when they do occur, it typically involves damage to the surrounding tissues. The ability to recognize and treat these complications is paramount for any surgeon that routinely places IPPs. Aim The aim of this article was to present a unique reservoir‐related complication as well as perform a literature review of reservoir‐related complications and techniques for reservoir placement, and provide a summary of dimensions and technical aspects of commonly used reservoirs. Methods We reviewed a unique reservoir‐related complication that presented to our institution with urinary retention and constipation. We also reviewed reservoir‐related complications since 1984, reviewed the most recent surgical techniques involved in reservoir placement, and summarized the dimensions and technical characteristics of both the American Medical System® and Coloplast® reservoirs. Main Outcome Measure A reservoir‐related complication that resulted in urinary retention and constipation is the main outcome measure. Results Although uncommon, reservoir complications do occur. The most common case report complication in the published literature is bladder erosion followed by external iliac compression, ileal conduit erosion, and small bowel obstruction. The case that presented at our institution was the result of a reservoir that was improperly placed in the perineum, causing urinary retention and constipation due to the compression of the bulbar urethra and rectum. Conclusions In this era, mechanical failures of IPP reservoirs are rare as most complications occur due to damage of the surrounding tissues. Prevention, diagnosis, and treatment of these complications are important for any surgeon that implants IPPs. Simon R, Hakky TS, Henry G, Perito P, Martinez D, Parker J, and Carrion RE. Tips and tricks of inflatable penile prosthesis reservoir placement: A case presentation and discussion. J Sex Med 2014;11:1325–1333.